Severity of Periodontitis and Metabolic Syndrome: Is There an Association?. Issue 4 (1st April 2016) - Gomes‐Filho, Isaac Suzart; das Mercês, Magno Conceição; de Santana Passos‐Soares, Johelle; Seixas da Cruz, Simone; Teixeira Ladeia, Ana Marice; Trindade, Soraya Castro; de Moraes Marcílio Cerqueira, Eneida; Freitas Coelho, Julita Maria; Marques Monteiro, Fernanda Maria; Barreto, Maurício Lima; Pereira Vianna, Maria Isabel; Nascimento Costa, Maria da Conceição; et al.
Abstract : Background: Metabolic syndrome (MetS) is a major factor for the occurrence of cardiovascular events. Causal factors for MetS are not well defined or yet unidentified. Preliminary investigations suggest that infections and inflammation may be involved in the etiology of this syndrome. This study aims to estimate the association between the severity of periodontitis (exposure) and MetS (outcome). Methods: A cross‐sectional study was conducted with 419 participants recruited from the Diabetes and Hypertensive Treatment Center, Feira de Santana, Bahia, Brazil. After administration of a questionnaire, general and oral clinical examination and laboratory tests were performed. Diagnosis of periodontitis and MetS was performed according to various criteria. The analysis of the effect of periodontitis on MetS used logistic regression analysis with adjustment for confounders. Results: The prevalence of periodontitis was found to be between 34.61% and 55.37%, depending on the classification definitions used, and the prevalence of MetS ranged from 60.86% to 67.06%. In the group with periodontitis, 14.08% had severe and 41.29% had moderate levels of periodontitis. There was an association between severe periodontitis and MetS after adjustment for sex, age, household density, alcoholic beverage consumption, smoking habit, and cardiovascular disease (odds ratio ORadjusted_6 = 2.11, 95% confidence interval = 1.01 to 4.40, P = 0.05). Conclusions: The results suggest that periodontitis is associated with MetS, and that MetS prevalence is related to severe periodontitis.